Is Sport Sustainable?—It Depends! - Tangen, Jan Ove (Frontiers in Sports and Active Living, 2021)
Is sport sustainable? Could sport be sustainable? Is there hope? The short answer is: it depends. This article discusses the six most essential issues on which answers to the questions above depend. First, it depends on what we already know about sport and sustainability. Second, it depends on how we observe or define sport and sustainability, respectively. Third, it depends on the ontology and epistemology on which the definitions and theories are based. Fourth, it depends on how we describe and explain the relationships and dependencies between sport, society and the environment. Fifth, it depends on how historical and sociological theories describe and explain how societies and civilizations operate, develop and eventually collapse. Sixth, it depends on whether we believe is it possible to plan and steer the future. These conditions indicate that the questions are challenging to answer but not impossible. Based on sociological systems theory, the author concludes that sport will not be sustainable unless modernity changes into a different kind of society—a world society that operates and governs from the binary code of sustainable/unsustainable instead of today's statal code of power/powerless.